The Little Harlequin Katydid-a new species of Paraxiphidium Redtenbacher, 1891 (Orthoptera: Tettigoniidae: Conocephalinae; Conocephalini) from the Amazonian Rainforest - DE Mello Mendes, Diego Matheus; DE Oliveira, Jomara Cavalcante (Zootaxa, 2019)
Paraxiphidium is a genus of flashy Neotropical katydids belonging to Conocephalini. Paraxiphidium iriodes sp. nov. is described from the Brazilian Amazon region. This is the first record of the genus for Brazil. The description of stridulatory file, male internal genitalia and data on natural history is provided. A key is included to the species of the group and a map with the geographical records completes the paper.Paraxiphidium is a genus of flashy Neotropical katydids belonging to Conocephalini. Paraxiphidium iriodes sp. nov. is described from the Brazilian Amazon region. This is the first record of the genus for Brazil. The description of stridulatory file, male internal genitalia and data on natural history is provided. A key is included to the species of the group and a map with the geographical records completes the paper.